Fatigue characterization of a crankshaft steel: Use and interaction of new models (Fracture and Structural Integrity, 2015)
The peculiar geometrical shape and working conditions of crankshafts make fatigue becoming responsible for most of the failure cases in such components. Therefore, improvement of crankshaft performance requires enhancing its fatigue life. In this work, the fatigue behavior of a D38MSV5S steel, used for crankshafts in compact vehicles, is investigated according to two traditional ways of analysis, namely the stress based and the fracture mechanics based approaches, though using advanced design models: On the one side, a probabilistic Weibull regression S-N model is assessed for experimental results obtained from fatigue resonance tests. On the other side, the crack growth rate curve is calculated from crack growth tests, carried out on SENB specimens, using a normalizing procedure. Specific Matlab programs are developed to facilitate the evaluation process. The information gained from both models will contribute to provide a probabilistic interpretation to the Kitagawa-Takahashi diagram.
Keywords: Fatigue of crankshafts; Crack growth rate curves